Religious Coping Used by Earthquake Survivors during Huge Earthquake in Türkiye - HÜSEYIN ÇAKSEN (Pakistan Journal of Medical & Health Sciences, 2024)
On 6 February 2023 a huge earthquake struck Türkiye with a magnitude of Mw 7.7. More than 10 million people in eleven cities have personally experienced the great and terrible and frightening shaking of the earthquake. In the earthquake, more than one hundred thousand people were injured and more than 50 thousand people died. Religion is a law enacted by Allah, which, by their own will, guides people of intelligence to goodness in this world and salvation in the hereafter . Religious coping is religiously framed cognitive, emotional, or behavioral responses to stress, encompassing multiple methods and purposes as well as positive and negative dimensions. Herein, we presented some examples of religious coping used by earthquake survivors during the huge earthquake in Türkiye to emphasize the importance of religion and spirituality.